The Role of Mental Work as a Mediator Between Work Stress and Employee Performance - Wijayadne, Devi Rahnjen; Lestari, Yetty Dwi; Yulianti, Praptini (RSF Conference Series: Business, Management and Social Sciences, 2024)
In an increasingly competitive and dynamic world of work, employee performance is a key factor in achieving organizational goals. However, high employee performance is often accompanied by an increase in workload which can cause work stress. This research aims to determine whether work stress has an influence on employee performance through mental workload, the second hypothesis that work mental load can directly influence employee performance, the third hypothesis that work stress has an influence on employee performance and the fourth hypothesis that work stress has an influence on work mental load. This research uses the method that work stress has an influence on employee performance through mental workload, the second hypothesis that work mental load can directly influence employee performance, the third hypothesis that work stress has an influence on employee performance and the fourth hypothesis that work stress has an influence on work mental load. The research method used is a quantitative method with a mediation analysis approach using the help of Smart PLS statistical software. The research results show that (1) mental workload can play a partial role as a mediator between work stress and employee performance, (2) work stress is able to directly influence employee performance, (3) work stress is able to influence mental workload, (4) mental workload can affect employee performance. The implication of this research is that organizations can develop a more holistic approach in managing work stress and mental workload.